Different Worlds Within Swedish Personal Social Services. Social Worker's Views on Conditions for Client Work in Different Organisational Models. - Marek Perlinski; Björn Blom; Stefan MorÃ©n (Social Work and Society)
The article presents a study of the personal social services' (PSS) organisation and economy as conditions for social workers' assessments of needs and appropriate interventions. One central aim was to study how different organisation models affect social workers' client work, especially concerning possibilities to establish supportive relationships with the clients.